Ta’tsîr Wasîlah as-Shûrah ’alâ Istî’âb al-Mufradât al-Lughah al-‘Arabiyyah - Rofi’ah, Wasilatur; Syaifullah, Muhammad; Nurkholis, Nurkholis; Pratiwi, Bety Dwi; Munawar, Endang (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
There are problems related to Arabic in students' vocabulary learning abilities, namely the lack of motivation to teach female students in learning vocabulary from different educational backgrounds and because students are not able to remember vocabulary well. With some of these problems, the researcher applied the image method to understand vocabulary in Arabic among class VII students at the Raudhah al-Qur'an boarding school. The method used in this research is the quantitative research method. The result of this research is that there is an effect of the image medium on the comprehension of the vocabulary of the Arabic language. The researchers suggested to the teacher of the Arabic language at the Raudhah Al-Qur’an Islamic Institute, Metro, that the use of an educational method such as the image method, which helps train female students in the ability of vocabulary in the Arabic language. The students should strive to learn, especially in the Arabic language vocabulary, in order to obtain good learning results.